Bayesian analyses of Yemeni mitochondrial genomes suggest multiple migration events with Africa and Western Eurasia. Issue 3 (14th November 2015) - Vyas, Deven N.; Kitchen, Andrew; Miró‐Herrans, Aida T.; Pearson, Laurel N.; Al‐Meeri, Ali; Mulligan, Connie J.
ABSTRACT: Objectives: Anatomically, modern humans are thought to have migrated out of Africa ∼60, 000 years ago in the first successful global dispersal. This initial migration may have passed through Yemen, a region that has experienced multiple migrations events with Africa and Eurasia throughout human history. We use Bayesian phylogenetics to determine how ancient and recent migrations have shaped Yemeni mitogenomic variation. Materials and Methods: We sequenced 113 mitogenomes from multiple Yemeni regions with a focus on haplogroups M, N, and L3(xM, N) as these groups have the oldest evolutionary history outside of Africa. We performed Bayesian evolutionary analyses to generate time‐measured phylogenies calibrated by Neanderthal and Denisovan mitogenomes in order to determine the age of Yemeni‐specific clades. Results: As defined by Yemeni monophyly, Yemeni in situ evolution is limited to the Holocene or latest Pleistocene (ages of clades in subhaplogroups L3b1a1a, L3h2, L3x1, M1a1f, M1a5, N1a1a3, and N1a3 range from 2 to 14 kya) and is often situated within broader Horn of Africa/southern Arabia in situ evolution (L3h2, L3x1, M1a1f, M1a5, and N1a1a3 ages range from 7 to 29 kya). Five subhaplogroups show no monophyly and are candidates for Holocene migration into Yemen (L0a2a2a, L3d1a1a, L3i2, M1a1b, and N1b1a). Discussion: Yemeni mitogenomes are largely the product of Holocene migration, and subsequent in situ evolution, from Africa and western Eurasia. However, we hypothesize that recent population movements may obscure the genetic signature of more ancient migrations. Additional research, e.g., analyses of Yemeni nuclear genetic data, is needed to better reconstruct the complex population and migration histories associated with Out of Africa. Am J Phys Anthropol 159:382–393, 2016. © 2015 Wiley Periodicals, Inc.